A kit and handbook for the study of simple electric circuits - Pascua, Gregorio A. 1938-
This paper is concerned with the design, construction, use and repair of a kit for the study of simple electric circuits. The study is comprised of two phases, namely: instrumentation and curriculum making in the sense that innovative curriculum materials in the form of a handbook and experiments have been written.